Cellular Structures of Mature Green Banana Musa AAB CV. ‘Rastali’ and Musa AAA CV. ‘Berangan’ - Ding, Phebe; Muhammad, H.; Abdul Razak, Abdul Rahman (2006)
Both mature of Musa AAA cv ‘Rastali and Musa AAA cv ‘Berangan’ consist of peel, peel-pulp transition and pulp regions. Epidermal cells from the outer layer of peel and were covered by cuticles and wax. Stomatal density of Rastali and Berangan banana was 360 and 400 stomatal/cm2, respectively. Inclusions that appeared in the peel of both bananas were i) vascular bundles surrounded by a ring of laticiferous ducts and ii) tannin bodies. Idioblast cells containing raphide were appeared in Berangan banana peel however Rastali banana did not contain these cells. Cuboid crystals were found dispersed abundantly in the peel cells of Rastali banana near the epidermal layer. The shape of crystal became elongated in the cells near the transition region. The transition region for both bananas was characterized by air apaces and starch granules containing cells. Most of the starch granules were in oval or rod shape. Inclusions that appeared in the pulp of both bananas were i) vascular bundles surrounded by a ring of laticiferous ducts. The size of starch granules in pulp was much bigger and denser as compared to those in transition region. The shape of pulp starch granules were mostly flat discs.